Polysomnographic Study to Evaluate Obstructive Sleep Apnoea Syndrome in Obese and Non Obese Adolescents - HP Arun Kumar; K Pushpa (Journal of Clinical and Diagnostic Research, 2021)
Introduction: Obesity in adolescents is an emerging problem in developing countries like India, especially among higher socioeconomic status group. Obesity is the most important reversible risk factor for Obstructive Sleep Apnoea Syndrome (OSAS) in adolescents. Adolescent obesity with OSAS if not treated, can result in serious morbidity in cognitive, cardiovascular, somatic growth, development and metabolic disorders in future. Aim: To compare the sleep pattern between the obese and non obese adolescents and to evaluate OSAS. Materials and Methods: This was an observational study carried out at Life Style Laboratory, Department of Physiology,Bangalore Medical College and Research Institute, Karnataka, India. The study involved 30 obese and 30 non obese male adolescents, who were subjected to overnight Polysomnography (PSG) in the sleep laboratory. According to Kale’s criteria, epochs were manually scored which were compiled and statistically analysed for parameters like Sleep Latency (SL), Actual Sleep Time (AST), wake after sleep onset, percentage of Non Rapid Eye Movement (NREM), Rapid Eye Movement (REM) sleep stages, Sleep Efficiency (SE). The number of apnoeas and hypopnoeas were also noted to calculate Apnoea Hypopnoea Index (AHI). These parameters were compared for statistical significance using student t-test. Adolescents with AHI ≥1 were diagnosed with OSAS. Results: Mean age of obese adolescents was 17.7±0.97 years and their mean BMI was 28±0.73 kg/m2 . OSAS was found in 22 out of 30 obese (73%) and 14 out of 30 (46%) non obese adolescents. It was found that apnoeas (3±4.80 vs 1±0.89), hypopnoeas (27.36±26.5 vs 5.46±2.97) and AHI (4.17±3.90 vs 0.89±0.43) were significantly more among obese adolescents when compared with non obese adolescents respectively. PSG parameters like SL, Wake After Sleep Onset (WASO) were prolonged and AST, SE were reduced significantly in obese adolescents. Conclusion: Adolescents with obesity had greater occurrence of OSAS, along with altered sleep architecture in them.